AN ANALYSIS OF CULTURAL DIFFERENCES AS SEEN IN KOREAN FILM MISS GRANNY (2014) AND ITS INDONESIAN REMAKE SWEET 20: - - Hanum Bella Ardya Garini Garini; Shafira Abigail Abigail; Dimas Getih Pangestu Pangestu; Adi Purnawan Purnawan (UIN Raden Mas Said Surakarta, 2022)
In recent years, there are a lot of popular Asian films or dramas that got Indonesian remake. It leads to cultural shifts between the original one and the remake version which receives a good reaction from the viewers. Among the Indonesian remake films, the researchers found a significant cultural shift in Sweet 20, 2017 Indonesian film which is produced based on a popular South Korean film, Miss Granny. The aim of this research is to reveal the cultural differences contained in the films Sweet 20 and Miss Granny. This research employs analysis descriptive analytical analysis as the technique to analyze the data and use the theory of transcultural adaptation by Linda Hutcheon (2006), Koentjaraningrat’s theory which concerns seven elements of cultures and supported by Bronislaw Malinowski. This research uses descriptive qualitative method because it is related to the data which are text and visual taken from the dialogues and visualizations in Miss Granny and Sweet 20 films. Meanwhile, the researchers apply three techniques for data collection: observation (watching the films), documentation (documenting the dialogues), and recording (screenshotting the scenes). After examining it, the researchers found five elements as cultural shifts between Miss Granny and Sweet 20; namely religious system, social norms, art, living equipment, and language.